2013
DOI: 10.4236/jbnb.2013.41013
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility, Biofilm Production and Adhesion to HEp-2 Cells of <i>Pseudomonas aeruginosa</i> Strains Isolated from Clinical Samples

Abstract: A hundred Pseudomonas aeruginosa strains from several clinical specimens from five hospitals in São Luís-MA were evaluated for biofilm production, prevalence of the gene algD, adhesion to HEp-2 cells and antimicrobial susceptibility. The most affected clinical specimens and hospital sectors were also evaluated. Most isolates were obtained from the tracheal aspirate (21.0%) and the most affected hospital sector was the ICU (43.0%). The antibiotics with the highest sensitivity rate were amikacin, piperacillin/ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Coproduction of AmpC and ESBL (3.9%) in the isolates of this study was similar to the findings of Upadhyay et al (3.3%), but much lower than several other reports (24.5-26%) ( 17 , 22 , 23 ). Finally, similar to a report from Brazil, the isolates of the present study did not harbor SHV and CTX-M genes ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…Coproduction of AmpC and ESBL (3.9%) in the isolates of this study was similar to the findings of Upadhyay et al (3.3%), but much lower than several other reports (24.5-26%) ( 17 , 22 , 23 ). Finally, similar to a report from Brazil, the isolates of the present study did not harbor SHV and CTX-M genes ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…In a study carried out by Banar et al [ 20 ], the frequency of these genes among 57 P. aeruginosa strains was as follows: algD (100%), pelF (93%), and pslD (54.6%). Also, in other studies conducted by Namuq et al, Ghadaksaz et al, and Zaranza et al, the frequency of the algD gene has been reported as 98%, 87.5%, and 39%, respectively [ 29 , 33 , 34 ]. Bacterial strains that carry the genes encoding the biofilm formation have the potential to cause severe infections.…”
Section: Discussionmentioning
confidence: 85%
“…The evaluation of capsule production was assessed by culturing the candida strains on Congo red agar (CRA) as described by (23) with minor modifications. The Congo red agar was prepared by mixing 36 g saccharose (Sigma Chemical Company, Lezennes, France) with 0.8 g Congo red in 1 L of on Tryptic Soy Agar (TSA, Difco, City, Spain) supplemented with NaCl (1.0%).…”
Section: Methodsmentioning
confidence: 99%
“…The plates were then inoculated with the Candida spp. and incubated aerobically for 24 h at 37ºC followed by another 24 h at 30 o C. After incubation, black colonies were considered as capsule producers, whereas red colonies were considered as non-producers (23). All tests were done in triplicates that are independent of each other.…”
Section: Determination Of Capsulase Formation Abilitymentioning
confidence: 99%